2011
DOI: 10.1177/1071181311551259
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Impact of Synthetic Speech on Unattended Recall in a Dichotic Listening Task

Abstract: Synthetic speech, which is generated by a computer, is widely used in both everyday situations (e.g. GPS devices; weather alerts) and the military (e.g. aviation). Synthetic speech is not identical to spoken speech, as it has a different pacing and varying pronunciations. Participants engaged in a Dichotic Listening Task in which they actively repeated information that was being presented in one ear, while ignoring their other (unattended) ear. The task was adapted and used both synthetic and spoken speech in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…The Sinatra, et al (2011) study was used as a guide for coding the reported unattended data. Two independent coders examined the reported information from the current study, and the original data, and coded it in three categories, each of which had a maximum possible score of 2.…”
Section: Results Codingmentioning
confidence: 99%
See 4 more Smart Citations
“…The Sinatra, et al (2011) study was used as a guide for coding the reported unattended data. Two independent coders examined the reported information from the current study, and the original data, and coded it in three categories, each of which had a maximum possible score of 2.…”
Section: Results Codingmentioning
confidence: 99%
“…However, more recent studies have indicated that some participants could report information about the content of their unattended ear (Sinatra, Sims, Najle, & Chin, 2011;Wood & Cowan, 1995). One possible reason for this difference is that the earlier dichotic listening studies tended to be less consistent with their unattended stimuli, which often were without context (e.g., numbers, unrelated words, newspaper articles).…”
Section: Dichotic Listeningmentioning
confidence: 88%
See 3 more Smart Citations